Morphospecies Abundance of Above-Ground Invertebrates in Agricultural Systems under Glyphosate and Microplastics in South-Eastern Mexico - Edilberto Hernández-Gutiérrez (MDPI AG, 2021)
Soil invertebrates are important for diverse soil ecosystem services, which are jeopardized by pesticides and microplastics. In the present study, we aimed to assess above-ground invertebrates’ morphospecies abundance in the presence of glyphosate (GLY), its main metabolite aminomethylphosphonic acid (AMPA), and microplastics (MPs). Three land-use systems were analyzed: agricultural systems with and without plastic mulch and pesticides (AwPM, AwoPM) and natural unmanaged farming systems (UF). Soil GLY, AMPA, MP concentrations and above-ground invertebrates were quantified. GLY concentrations were also assessed inside invertebrate tissues. GLY, AMPA and the highest concentration of GLY in invertebrates’ tissue were found only in AwoPM at 0.14–0.45 mg kg−1, 0.12–0.94 mg kg−1 and 0.03–0.26 mg kg−1, respectively. MPs were present as follows: AwPM system (100%, 400–2000 particles kg−1) > AwoPM (70.8%, 200–1000 particles kg−1) > UF (37.5%, 200–400 particles kg−1). No significant correlations were found between soil MPs, GLY and AMPA. There was a significant correlation between MPs and morphospecies from the order Entomobrymorpha (Collembola, R = 0.61, p < 0.05). Limnophila, Mesogastropoda (Gastropoda) and Siphonaptera morphospecies were only present in the UF system. GLY in invertebrate tissue was inversely correlated with soil GLY (R = −0.73, p < 0.05) and AMPA (R = −0.59, p < 0.05). Further investigations are required to understand these phenomena.